Determinan Corporate Social Responsibility (CSR) dalam Laporan Tahunan Perusahaan - Neneng Sri Suprihatin; Kodriyah Kodriyah; Dyah Ayu Pradaningrum (ITB AAS INDONESIA, 2023)
issues, especially large companies in Indonesia, show that they tend to be an important spotlight regarding their environmental activities, both those related to the environment, society, and the welfare of the company's employees themselves. As a result, many companies that deal directly or indirectly with the community must pay attention to their environmental problems to satisfy stakeholder interests. And some of these issues we can conclude that Corporate Social Responsibility is indispensable in the industrial world inorder to be responsible for the activities carried out by a company towards the environment and stakeholders. The purpose of this study was to examine the Determinants of Corporate Social Responsibility (CSR) Disclosure in the Company's Annual Report (Empirical Study of Basic and Chemical Manufacturing Companies in the IDX 2016-2020). The sampling method used is purposive sampling with a total of 24 companies as samples. The data analysis method used is multiple linear regression analysis and processed using SPSS 25. The test results show that: (1) company age has no significant effect on disclosure of social responsibility, and (2) ownership proportion structure has a negative and significant effect on disclosure of responsibility. social responsibility, (3) the age of the company has no significant effect on the disclosure of social responsibility, (4) media exposure has a significant effect on the disclosure of social responsibility, and (5) audit quality has no significant effect on the disclosure of social responsibility.